Shock finding on a moving-mesh – II. Hydrodynamic shocks in the Illustris universe. Issue 4 (4th July 2016) - Schaal, Kevin; Springel, Volker; Pakmor, Rüdiger; Pfrommer, Christoph; Nelson, Dylan; Vogelsberger, Mark; Genel, Shy; Pillepich, Annalisa; Sijacki, Debora; Hernquist, Lars
Abstract : Hydrodynamical shocks are a manifestation of the non-linearity of the Euler equations and play a fundamental role in cosmological gas dynamics. In this work, we identify and analyse shocks in the Illustris simulation, and contrast the results with those of non-radiative runs. We show that simulations with more comprehensive physical models of galaxy formation pose new challenges for shock finding algorithms due to radiative cooling and star-forming processes, prompting us to develop a number of methodology improvements. We find in Illustris a total shock surface area which is about 1.4 times larger at the present epoch compared to non-radiative runs, and an energy dissipation rate at shocks which is higher by a factor of around 7. Remarkably, shocks with Mach numbers above and below $\mathcal {M}≈ 10$ contribute about equally to the total dissipation across cosmic time. This is in sharp contrast to non-radiative simulations, and we demonstrate that a large part of the difference arises due to strong black hole radio-mode feedback in Illustris. We also provide an overview of the large diversity of shock morphologies, which includes complex networks of halo-internal shocks, shocks on to cosmic sheets, feedback shocks due to black holes and galactic winds, as well as ubiquitous accretion shocks. In high-redshift systems more massive than 10 12 M⊙, we discover the existence of a double accretion shock pattern in haloes. They are created when gas streams along filaments without being shocked at the outer accretion shock, but then forms a second, roughly spherical accretion shock further inside.